Designing and construction of access road to Ladang Besout Jaya, Mukim Sungkai Daerah Batang Padang, Perak Darul Ridzuan, trough Sim Darby Plantation Sdn.Bhd / Nur Sahida Abdul Rahman - Abdul Rahman, Nur Sahida (2015)
This report is study to know and learn about the process, methods also design to make the Road Pavement (Pemix) known as “Road Tar”. It links the theory they have learned to actual work on site. This report shows how the work undertaken at the site as a premix works, testing of premix, placement, compaction, and many more are there in the body on this report. In this study, to be seen whether the work carried out on site according to specifications or not. Based on these studies can make comparisons about what they have learned from theory and also learn from the practical. This is based on observations from several studies on the construction site. In carrying out the works on site most of the work is done by construction workers, not according to specifications and the most dissatisfied are concerned about their safety while typing work. Therefore, this should be taken seriously as it relates to the quality and management work. By writing this report, it is hoped that relevant parties can be take more attention for their high quality project.